PENGARUH LOCUS OF CONTROL DAN PROSEDUR REVIEW TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT PADA KAP DI SURABAYA - Putri, Dian Atmaja (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to test the influence of locus of control and review procedure to the premature termination of auditing procedure. The research population is KAP auditors in Surabaya with the samples are 50 respondents. The data collection is conducted by distributing questionnaires to the auditorsâ respondents; the hypothesis test is done by using the multiple regressions method. The research result shows that locus of control and review procedure has significant influence to the premature termination of auditing procedure. Auditors who have external locus of control are tend to perform premature termination of auditing procedure while premature termination on infective audit procedure allows the premature termination to occur on auditing procedure. Keywords: Locus of Control, Review Procedure, Auditing Procedure.